Pengaruh Suku Bunga Terhadap Inflasi dan Pertumbuhan Ekonomi Di Indonesia - Pratiwi, I Gusti Ayu Made Agung Mas Andriani (Jurnal Ilmiah Sains Sosial, Kewirausahaan dan Kebudayaan, 2024)
The Covid-19 outbreak dealt a severe blow to Indonesia's economy. The global economic conditions were similarly affected, and Indonesia was no exception. Data shows that over the past five years, inflation and Indonesia's economic development have experienced fluctuations. Monetary policy, particularly interest rates, and inflation are two elements that influence economic growth. This research combines time series data from 2019 to 2023 using secondary data from Indonesia's Central Bureau of Statistics (BPS). The study employs quantitative and descriptive analytical methods using the structural equation modeling (SEM) approach, specifically Partial Least Square (PLS). The research findings indicate that: (1) interest rates have a positive and significant effect on inflation; (2) interest rates have a positive but insignificant effect on economic growth; and (3) inflation acts as a mediator between interest rates and economic growth in Indonesia.